Proto-state media systems: the digital rise of Al-Qaeda and ISIS - Winkler, Carol (Causes and consequences of terrorism series, 2022)
Proto-State Media Systems explores how decisions by contemporary violent extremist groups create, develop, and sustain media systems. Focusing on the cases of al-Qaeda and ISIS, this book showcases how standard media systems theory fails to fully explain the media systems of these organizations as a basis for building a revised theoretical lens that comprehends these emergent systems in the 21st century global media context. Utilizing constitutive and online networking theories, Winkler and El Damanhoury explore how militant proto-states create lasting, adaptable, identity-based systems that work to attract and sustain the attention of followers. The groups' appeals to transhistorical and transpatial identity formations in their media products reveal new insights about community formation and how we analyze media systems in the proto-state context. Recognizing that nation-states no longer exercise monopoly control over online and offline media systems, Proto-State Media Systems investigates how certain violent extremist groups bent on establishing sustained territorial and governing control over populations have revolutionized the media environment of the 21st century.